Response of Seasonally Frozen Ground to Climate Changes in the Northeastern Qinghai-Tibet Plateau - Zhao, Zhihui; Fu, Ruiyu; Liu, Junjie; Dai, Licong; Guo, Xiaowei; Du, Yangong; Hu, Zhongmin; Cao, Guangmin (Frontiers in Environmental Science, 2022)
The effects of climate change on permafrost have been well documented in many studies, whereas the effect of climate change on seasonally frozen ground (SFG) is still poorly understood. We used the observed daily freeze depth of SFG and environmental factors data from the period 2007–2016 to examine the seasonal and inter-annual variation of SFG. We quantitatively evaluated the effects of environmental factors on SFG using the boosted regression trees analysis. The results show that on a seasonal scale, the lower layer soil frost starts freezing in mid-November, with the maximum freeze depth occurring in late March (209 cm), and then begins to thaw at both the lower and upper layers. We identified four stages of the freeze-thaw cycle: the non-frozen phase, initial freezing, deep freezing, and thawing. Furthermore, the thawing process of SFG mainly took place in the upper layer, but the freezing rate of the lower layer from mid-November to early February was similar to the thawing rate of late April to late June. On the inter-annual scale, the maximum freeze depth showed a significant increasing trend (P < 0.05). However, the freeze-thaw duration declined significantly (P < 0.05), which was correlated with the decrease in the period when surface soil temperature is below 0℃. The mean soil temperature and soil heat flux were the most important environmental indicators affecting seasonal variation of SFG depth, and the cumulative negative air and soil temperatures were the dominant factors affecting inter-annual variation of maximum freeze depth. Our results might provide insight for predicting hydrological and ecological responses to future climate change in frozen-ground regions.